Historical water environment changes in Chagan Lake (mid-19th to mid-20th century) inferred from sedimentary diatom records - Fengyang Sui; Fengyang Sui; Xinxin Du; Henglin Xiao; Henglin Xiao; Shuying Zang; Hongkuan Hui; Qi Lv; Yan Liu; Nannan Zhang; Yawen Fan (Frontiers in Ecology and Evolution)
Chagan Lake is the largest meadow-type lake in Northeast China. Over the past century, due to anthropogenic disturbances and regional environmental changes, its aquatic ecosystem has suffered significant stress. This study used sediment diatom records, 210Pb dating, and ecological classification indices to reconstruct the historical water environment changes of Chagan Lake from the mid-19th century to the mid-20th century. Two distinct ecological phases were identified: (1) Zone I (ca. 1859–1950 CE) recorded stable, weak alkaline (pH classes 3–4) and fresh-brackish (salinity class around 2) conditions, with diatoms Aulacoseira granulata (43–72%) and Aulacoseira ambigua (4–17%) being dominant, indicating a moderately eutrophic state with a relatively low level of organic pollution. (2) Zone II (ca. 1951–1962 CE) marked a transition to fluctuating conditions, with a sharp decline in A. granulata (16–36%) and an increase in pollution-tolerant taxa (such as Stephanocyclus meneghinianus: 2–32%, Nitzschia palea: 7–20%), and changes in oxygen requirements (classes 2–3 to 2–4), saprobity (classes 1–2 to 2–3), nitrogen metabolism (classes 1–2 to 1–3), and trophic state (classes 4–5 to 5). Hierarchical clustering and principal component analysis confirmed that significant changes occurred in the diatom community around the 1950s, associated with population growth, increased agricultural runoff, and altered hydrological conditions. Although pH values and salinity thresholds remained stable, the nutrient status developed towards eutrophication after the 1950s. Sedimentological data further indicated accelerated sedimentation rates (0.34 cm·yr−1 pre-1950s vs. 1.31 cm·yr−1 post-1980s) and notable changes in grain-size characteristics, attributable to combined anthropogenic erosion, hydrological engineering, and climatic influences. These findings established a baseline for understanding the anthropogenic impacts on Chagan Lake over a century scale and emphasized the urgency of adopting targeted restoration strategies for shallow, semi-arid lake ecosystems facing similar stressors.